Complicated appendicitis and associated risk factors among children - Molla Azmeraw; Biruk Beletew Abate; Dessie Temesgen; Sefineh Fenta Feleke; Ribka Nigatu Haile; Melsew Dagne Abate; Tegene Atamenta Kitaw (BMC Pediatrics)
Abstract Background Complicated appendicitis is one of significant pediatric surgical care challenges and its burden varied from 5 to 75%. However, there is limited study about prevalence of complicated appendicitis among children in Ethiopia. Therefore, this study aimed to assess the prevalence and associated factors of complicated appendicitis among children in Amhara region, Ethiopia. Methodology A cross-sectional study design was employed. The data extraction tool was used to collect data from 423 sampled participants. Simple random sampling technique was used. The data was presented using table, and text forms. The data was also summarized by proportion and frequency depends on the data type. The logistic model was fitted. Any statistical test considered significant at P-value < 0.05. Result A total of 406 study participants were included for analysis. The prevalence of complicated appendicitis was 32.02%, 95%CI(27.64%, 36.74%). Duration of symptom greater than 24 h, aOR = 1.64, 95% CI (1.01,2.66)), and white blood cell count greater than 12,000 cells/µl aOR = 2.08, 95% CI (1.15,3.77) were statistically significant predictors of complicated appendicitis in children. Conclusion and recommendation The prevalence of complicated appendicitis was high as compared to the previous studies. Patient presentation after 24 h of symptom and white blood cell greater than 12000 cells/µl were significantly associated with complicated appendicitis. The surgical teams need to be aware that those children with greater white blood cell count and a chief compliant duration of greater than one day were present with complicated appendicitis.